Antiplatelet therapy in cardiovascular disease. Issue 941 (11th March 2004) - Behan, M W H; Storey, R F
Abstract : Platelet activation and aggregation are considered to be central to arterial thrombus formation. Antiplatelet therapy is therefore important for both the treatment and prevention of cardiovascular disease. Aspirin, the most widely used antiplatelet agent, inhibits platelet cyclo-oxygenase and the conversion of arachidonic acid to the potent platelet agonist thromboxane A2 but does not prevent platelet activation occurring via various signalling pathways that are independent of thromboxane A2 release. Therefore a number of other compounds have been developed to complement aspirin's beneficial effect. These include the thienopyridines (clopidogrel and ticlopidine), dipyridamole, and the αIIb β3 (glycoprotein IIb/IIIa) receptor inhibitors.